Application of Occupational Safety and Health in Cargo Handling by PT. Mulio Citra Angkasa at H. Asan Sampit Airport - Nurhafifa Nurhafifa; Teguh Ariebowo (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Occupational Health and Safety are all efforts and thoughts made in the context of preventing, overcoming and reducing the occurrence of accidents and their impacts through the steps of identifying, analyzing and controlling hazards by implementing an appropriate hazard control system and implementing legislation concerning occupational safety and health. . The purpose of this study is to find out the implementation of the implementation of Occupational Safety and Health (K3) in cargo handling by PT. Mulio Citra Angkasa (MCA) at H. Asan Sampit airport. The method used in this study is using qualitative research methods where researchers conduct interviews, documentation, and direct observation in data collection. The interviews used were semi-structured interviews and the researchers conducted interviews with managers, supervisors and senior cargo executive staff at PT. Space Imagery Master. Researchers went directly to the field in conducting direct observations to see the activities of the cargo operational unit and observing the implementation of Occupational Safety and Health (K3) when handling cargo. Researchers also conducted documentation in the form of interviews and documentation. The result of this research is the Application of Occupational Safety and Health (K3) in cargo handling by PT. Mulio Citra Angkasa at H. Asan Sampit Airport that there is still a lack of application of K3 in cargo handling. The deficiencies in the implementation were due to the unavailability of K3 experts and there were several violations committed such as negligence in the use of personal protective equipment (PPE) by cargo personnel.